Welfare redistribution through flexibility: Who pays? - Polina Emelianova; Nils Namockel (Institute of Energy Economics at the University of Cologne (EWI), 2024)
As part of the German energy transition, the increasing adoption of electricity-driven technologies in end- use sectors has become a key political priority. Decentralized rexibility from assets such as electric vehicles and heat pumps inruences electricity price formation, raising new challenges related to the redistribution of welfare gains, not only between producers and consumers but also across different groups within these two categories. This paper addresses two research questions: How does decentralized rexibility affect the redistribution of total system welfare between producers and consumers in the wholesale electricity market? And how do varying degrees of rexibility impact electricity costs across different user groups in the transport and heating sectors? To explore these questions, we enhance a European high-resolution dispatch model, focusing speciîocally on Germany, and incorporate a range of rexibility options and heterogeneous end-user groups. We further simulate multiple use cases with varying degrees of rexibility in the road transport and heating sectors. Our îondings reveal that while total system welfare improves slightly, increased rexibility redistributes welfare from producers to consumers. This redistribution beneîots consumers as an aggregated group by reducing electricity procurement costs, regardless of whether they provide rexibility. Among the rexibility options analyzed, electric vehicles - particularly through bidirectional charging - demonstrates a greater potential for welfare gains compared to heat pumps. However, this dynamic intensiîoes competition with centralized assets like utility-scale batteries. In the transport sector, rexibility leads to notable vari- ations in electricity costs based on charging behaviors, whereas in the heating sector, increased rexibility promotes cost convergence across different user groups.
Keywords: C61; D47; O33; Q41; Q48; 330; Flexibility; Welfare effects; Energy System Modeling; Energy Transition; End-use Sectors